2021
DOI: 10.1002/jsfa.11659
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐frying oil induces cytotoxicity, inflammation and apoptosis on intestinal epithelial cells

Abstract: BACKGROUND Deep‐frying oil has been found to cause inflammatory bowel disease (IBD). However, the molecular mechanism of the effect of deep‐frying palm oil on IBD still remains undetermined. RESULTS In the present study, bioinformatics and cell biology were used to investigate the functions and signal pathway enrichments of differentially expressed genes. The bioinformatics analysis of three original microarray datasets (GSE73661, GSE75214 and GSE126124) in the NCBI‐Gene Expression Omnibus database showed 17 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Previous studies suggested that oxidized triglyceride monomers exhibit potent cytotoxicity in biological safety of polar components in deep-frying oil. 15 Therefore, silica gel column chromatography and gel exclusion chromatography were applied to separate polar components and oxidized triglyceride monomers. Figure 2B,C shows the composition and content of oxidized triglyceride monomers in PO, HOPO, and SFO samples over time.…”
Section: Oxidized Triglyceride Monomer Compositionmentioning
confidence: 78%
See 2 more Smart Citations
“…Previous studies suggested that oxidized triglyceride monomers exhibit potent cytotoxicity in biological safety of polar components in deep-frying oil. 15 Therefore, silica gel column chromatography and gel exclusion chromatography were applied to separate polar components and oxidized triglyceride monomers. Figure 2B,C shows the composition and content of oxidized triglyceride monomers in PO, HOPO, and SFO samples over time.…”
Section: Oxidized Triglyceride Monomer Compositionmentioning
confidence: 78%
“…Deep-frying oil and TPC analysis was performed, separated, and determined as the previous studies described. , Briefly, 5 L of fresh oil was put into a commercial electric fryer (24 × 30 × 14 cm) and the fryer was heated to a constant temperature of 180 ± 5 °C for 10 h every day until the polar component content reached 25%. The extent of lipid peroxidation was determined by assaying the acidic value (AV), peroxide value (POV), and TPC, which were determined according to the AOAC official method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al found deepfrying oil, especially TPC, induced disorder of glucose and lipid metabolism in Kunming mice (Li et al, 2017). Li et al suggested that TPC could induce cytotoxicity, inflammation and apoptosis of Caco-2 cell (Li et al, 2021). Developing a full picture of deep-frying oil biosafety function requires an understanding of the digestion and absorption characteristics of TPC in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…The gastrointestinal tract also provides a large surface for exposure to environmental risk factors that can trigger intestinal inflammation, leaky gut, exposure to bacterial pathogens and endotoxins, immune response, neuroinflammation, and eventually Lewy pathology in PD (5). Consumption of artificial sweeteners, alcoholic beverages, fried foods, and processed foods are associated with disrupting intestinal integrity, leading to barrier dysfunction and malabsorption (6)(7)(8). Diet is one of the several environmental risk factors closely linked with PD pathology and disease progression.…”
Section: Introductionmentioning
confidence: 99%